Best Proximity Point Results for MK-Proximal Contractions - Mohamed Jleli; Erdal Karapınar; Bessem Samet (Abstract and Applied Analysis)
Let A and B be nonempty subsets of a metric space with the distance function d, and T:A→B is a given non-self-mapping. The purpose of this paper is to solve the nonlinear programming problem that consists in minimizing the real-valued function x↦d(x,Tx), where T belongs to a new class of contractive mappings. We provide also an iterative algorithm to find a solution of such optimization problems.